Costs and quality of life in a randomized trial comparing minimally invasive and open distal pancreatectomy (LEOPARD trial). Issue 7 (23rd April 2019) - van Hilst, J.; Strating, E. A.; de Rooij, T.; Daams, F.; Festen, S.; Groot Koerkamp, B.; Klaase, J. M.; Luyer, M.; Dijkgraaf, M. G.; Besselink, M. G.; ,
Abstract : Background: Minimally invasive distal pancreatectomy decreases time to functional recovery compared with open distal pancreatectomy, but the cost‐effectiveness and impact on disease‐specific quality of life have yet to be established. Methods: The LEOPARD trial randomized patients to minimally invasive (robot‐assisted or laparoscopic) or open distal pancreatectomy in 14 Dutch centres between April 2015 and March 2017. Use of hospital healthcare resources, complications and disease‐specific quality of life were recorded up to 1 year after surgery. Unit costs of hospital healthcare resources were determined, and cost‐effectiveness and cost–utility analyses were performed. Primary outcomes were the costs per day earlier functional recovery and per quality‐adjusted life‐year. Results: All 104 patients who had a distal pancreatectomy (48 minimally invasive and 56 open) in the trial were included in this study. Patients who underwent a robot‐assisted procedure were excluded from the cost analysis. Total medical costs were comparable after laparoscopic and open distal pancreatectomy (mean difference €–427 (95 per cent bias‐corrected and accelerated confidence interval €–4700 to 3613; P = 0·839). Laparoscopic distal pancreatectomy was shown to have a probability of at least 0·566 of being more cost‐effective than the open approach at a willingness‐to‐pay threshold of €0 per day of earlier recovery, and a probability of 0·676 per additional quality‐adjusted life‐year at a willingness‐to‐pay threshold of €80 000. There were no significant differences in cosmetic satisfaction scores (median 9 (i.q.r. 5·75–10) versus 7 (4–8·75); P = 0·056) and disease‐specific quality of life after minimally invasive (laparoscopic and robot‐assisted procedures) versus open distal pancreatectomy. Conclusion: Laparoscopic distal pancreatectomy was at least as cost‐effective as open distal pancreatectomy in terms of time to functional recovery and quality‐adjusted life‐years. Cosmesis and quality of life were similar in the two groups 1 year after surgery. Abstract : Laparoscopic distal pancreatectomy decreases time to functional recovery compared with open distal pancreatectomy, but the cost‐effectiveness has yet to be established. A cost‐effectiveness study was performed showing that laparoscopic distal pancreatectomy was at least as cost‐effective as the open approach in terms of time to functional recovery and quality‐adjusted life‐years. Similar cost utility and quality of life